Kajian Paket Pemupukan terhadap Usahatani Kedelai pada Lahan Kering Sulawesi Tenggara - Wahab, Abdul; Adnan, A. M.; Sarjoni, Sarjoni; Karimuna, Siti Rahmah (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Soybean consumption continues to increase along with the increase in population, so most must be imported because domestic production is insufficient. According to the Agricultural Research and Development Agency (2007) to meet domestic soybean needs to suppress imports, an increase in planting area of 7.25% is needed per year. This study aims to obtain a site-specific fertilizer technology package to support the development of soybeans on dry land in Southeast Sulawesi. This research was conducted in Ahuanguria Village, Baito District, South Konawe Regency, Southeast Sulawesi Province. The activity starts from January to December 2017, using a Randomized Block Design (RBD) with each of the 5 fertilization technology packages, consisting of 225 kg NPK / Ha + 25 kg urea / ha + organic fertilizer 2 t / ha + dolomite 0.65 t / ha; NPK 200 kg / ha + urea 25 kg / ha + organic fertilizer 2 t / ha + dolomite 0.65 t / ha (recommendation); NPK 175 kg / ha + urea 25 kg / ha + organic fertilizer 2 t / ha + dolomite 0.65 t / ha; NPK 150 kg / Ha + urea 25 kg / ha + organic fertilizer 2 t / ha + dolomite 0.65 t / ha; and control (existing technology). The application of location-specific fertilization technology packages on acidic dry land soybean plants significantly increased soybean growth and yield compared to controls. The treatment of NPK 225 kg / ha + urea fertilization package 25 kg / ha + organic fertilizer 2 t / ha + dolomite 0.65 t / ha shows the yield per hectare is 1.40 tons.